2019
DOI: 10.5114/wiitm.2019.89830
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bowel habits after laparoscopic sleeve gastrectomy.

Abstract: Introduction Bariatric surgery has a significant impact on dietary intake, weight loss, patient’s metabolism and also on defaecation stereotypes. Aim To investigate changes in bowel habits of morbidly obese patients after laparoscopic sleeve gastrectomy (LSG). Material and methods This was a prospective clinical cohort study conducted to assess changes in bowel habits after LSG in a single institution. Results In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Occasional adverse GI symptoms in our patients’ group were minimal, with constipation and vomiting being more prevalent at 3 months but improving over time. These findings align with Ostruszka et al [ 20 ]. Postoperative vomiting is common in 30% to 60% of MBS patients during the initial months, primarily due to the reduced stomach size [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…Occasional adverse GI symptoms in our patients’ group were minimal, with constipation and vomiting being more prevalent at 3 months but improving over time. These findings align with Ostruszka et al [ 20 ]. Postoperative vomiting is common in 30% to 60% of MBS patients during the initial months, primarily due to the reduced stomach size [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…One study found that six months sleeve gastrectomy, the overall rate of bowel disturbance in patients decreased from 58.8% to 13.2% before surgery [28] . These ndings suggest that patient weight loss after LSG may be associated with improvement in constipation symptoms for individual patients [29] .…”
Section: Negative Experiencesmentioning
confidence: 74%